Long-term follow-up after treatment of tubercular uveitis: case series and review of the literature - Putera, Ikhwanuliman; van Daele, Paul L. A.; ten Berge, Josianne C. E. M.; Dik, Willem A.; La Distia Nora, Rina; van Hagen, P. Martin; Rombach, Saskia M. (Frontiers in Ophthalmology, 2023)
Introduction: There is a scarcity of long-term follow-up data and management strategies for recurrent uveitis in tubercular uveitis (TBU), especially in cases extending beyond 10 years after the completion of initial antitubercular treatment (ATT).Methods: This retrospective study involved five TBU patients who were initially treated with combination of four-drug ATT for six months and five of them having more than 10 years of follow-up after uveitis resolution upon ATT completion. We describe the occurrence of recurrent uveitis and present our approach to managing these recurrent episodes.Results: Recurrent uveitis and CME developed in three out of five included TBU patients with a median of 18 years (range 13-20 years) follow-up. The anatomical sites of the recurrences were anterior, intermediate, and pan-uveitis. The recurrent episodes varied from 6 to 15 years after ATT completion. Systemic or local corticosteroids/ immunosuppressants successfully resolved all recurrent episodes, but one was also treated with the combination of isoniazid monotherapy again.Two patients needed anti-tumor necrosis factor-α therapy.Long-term monitoring of TBU patients after ATT completion is warranted. Further well-designed studies with larger sample sizes are required to better estimate the risk of recurrences, investigate the underlying mechanism of recurrences, and identify biomarkers that predict who is at risk for recurrences.